Distributed modeling of six-port transformer for millimeter-wave SiGe BiCMOS circuits design - Hou, Debin (2013)
In this paper, a six-port distributed model of on-chip single-turn transformers in silicon that can predict the features of the transformers up to 200 GHz is presented. Moreover, the proposed model is scalable with the diameter of the transformer. Based on the developed model, a transformer balun with improved differential-port balance is deployed in a D-band up-conversion mixer design in 0.13-μm SiGe BiCMOS technology. The mixer achieves a measured conversion gain (CG) of 4 ~ 7 dB and local-oscillator-to-RF isolation over 30 dB from 110 to 140 GHz. The results have one of the best CGs in the millimeter-wave range. A D-band two-stage transformer-coupled power amplifier (PA) integrated with a mixer is also reported here. Using the six-port transformer model, the performance of the PA can be conveniently optimized. At a 2-V supply, the gain and saturated output power of 20 dB and 8 dBm, respectively, are both experimentally achieved at 127 GHz. At 3 V, the measured output power rose to 11 dBm and this is the best power performance among the reported D-band silicon-based amplifiers to date.